What is the impact of the economic crisis on democracy? Evidence from Europe. Issue 5 (November 2016) - Morlino, Leonardo; Quaranta, Mario
There are already a number of good accounts of the impact of the recent 2008–2014 economic crisis on European democracies. However, no systematic assessments of how it has affected specific aspects of democracy have so far been carried out. We explore its impact on European democracies in several areas by adopting the 'quality of democracy' framework. Our analysis shows that the measures we employ capture the variation in quality during this 'troubled' period. The empirical analysis suggests that a shrinking of private and public resources due to an economic downturn prompts three reactions: (a) a general deterioration of the rule of law; (b) citizens become more sensitive about what governments deliver; and (c) detachment from the institutional channels of representation along with a choice to protest.